Toma de decisiones administrativas y financieras en la producción agrícola familiar en la provincia centro de Boyacá (2023)
Agricultural families make decisions whether administrative, financial or on cultivation through a complex process involving several elements. First, they gain experience in crops through observation and learning of agricultural techniques passed from generation to generation, which are efficient and adapted to their environment. Agricultural families often use their traditional knowledge, adapted to their local conditions and available resources.